2016
DOI: 10.5543/tkda.2016.44459
|View full text |Cite
|
Sign up to set email alerts
|

The effect of obesity and serum leptin levels on clopidogrel resistance

Abstract: Clopidogrel resistance is more common in obese and hyperleptinemic patients. Dosage should be individualized in these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…All of the abovementioned mechanisms are potentially responsible for a decreased reactivity of clopidogrel. 29 , 30 As such, we speculate that the CC genotype of GNAS rs7121 regulates clopidogrel resistance, thereby affecting the responsiveness of related drugs via inflammation related to body obesity.…”
Section: Discussionmentioning
confidence: 91%
“…All of the abovementioned mechanisms are potentially responsible for a decreased reactivity of clopidogrel. 29 , 30 As such, we speculate that the CC genotype of GNAS rs7121 regulates clopidogrel resistance, thereby affecting the responsiveness of related drugs via inflammation related to body obesity.…”
Section: Discussionmentioning
confidence: 91%
“…Many clinical studies have shown that obesity and hyperlipidemia are closely related to cardiovascular diseases such as hypertension and atherosclerosis. Doğan et al 22 found a significantly increased incidence of clopidogrel resistance in patients with BMI > 30. Comparison of the baseline data in the present study identified significant differences between the two Han groups in cholesterol and BMI levels, which is consistent with the results of Doğan et al's study; however, significant differences were not found between the two Hui groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that obesity is associated with a large number of co‐morbidities, with the most prominent being Type 2 diabetes mellitus and metabolic syndromes. Clinical research studies demonstrated that obesity is an independent risk factor for attenuated responses of platelets to clopidogrel in clinical settings (Dogan et al, 2016; Gajos & Mostowik, 2015; Norgard & Monte, 2017). However, sporadic and incomplete evidence indicated that diminished P450‐mediated metabolic activation of clopidogrel, augmented CES1‐catalyzed hydrolysis of the drug, the inflammatory status related to obesity, increased platelet turnover, and enhanced platelet reactivity all would contribute to poor responses to clopidogrel, to an extent that may vary in each patient involved (Norgard & Monte, 2017).…”
Section: Discussionmentioning
confidence: 99%